2013
DOI: 10.3168/jds.2012-6274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of castration method on neurohormonal and electroencephalographic stress indicators in Holstein calves of different ages

Abstract: As public concern for food animal welfare increases, a need to validate objective pain assessment tools exists in order to formulate animal welfare policies and facilitate regulatory approval of compounds to alleviate pain in livestock in the United States. The aims of this study were (1) to compare the physiological response to pain induced by surgical and nonsurgical (band) castration in calves and (2) to elucidate age-related differences in pain response of calves subjected to different castration methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 35 publications
4
72
1
4
Order By: Relevance
“…Stewart et al (2010a and2010b) and Dockweiler et al (2013) described an increase of eye temperature in calves right after castration (up to 10 min) due to an increase in parasympathetic nervous system activity associated with deep visceral pain. Results from these studies suggest that it would be beneficial to investigate eye temperature in a closer time interval to castration increasing the number of samplings but at the same time avoiding repeated handling that would not allow discrimination between pain and handling stress.…”
Section: Discussionmentioning
confidence: 99%
“…Stewart et al (2010a and2010b) and Dockweiler et al (2013) described an increase of eye temperature in calves right after castration (up to 10 min) due to an increase in parasympathetic nervous system activity associated with deep visceral pain. Results from these studies suggest that it would be beneficial to investigate eye temperature in a closer time interval to castration increasing the number of samplings but at the same time avoiding repeated handling that would not allow discrimination between pain and handling stress.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid chromatography-tandem mass spectrometry SP [1][2][3][4][5][6][7][8][9][10][11] Parent substance P molecule composed of 11 amino acids SP [3][4][5][6][7][8][9][10][11] Metabolite of substance P composed of the last 9 C-terminal amino acids SP [7][8][9][10][11] Metabolite of substance P composed of the last 5 C-terminal amino acids been evaluated as a response variable that may be more specific for the measurement of pain in animals. [3][4][5][6][7][8][9][10] Substance P is a biologically active peptide that has a role in neural transmission of nociceptive signals from peripheral sites to the CNS.…”
Section: Kiu Kallikrein Inhibitor Units Lc-ms-msmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Substance P is a biologically active peptide that has a role in neural transmission of nociceptive signals from peripheral sites to the CNS. 11 Substance P is released by peptidergic peripheral sensory nerve fibers at central synaptic junctions in the dorsal horn of the spinal cord and at peripheral nerve terminals, where the peptide has a role as a signaling molecule in the transmission of pain impulses and the induction of inflammation and central sensitization.…”
Section: Kiu Kallikrein Inhibitor Units Lc-ms-msmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in plasma PGE 2 was found in cattle that were dehorned (Fraccaro et al, 2013). Substance P had been used in assessing various routine procedures in cattle, such as castration (Coetzee et al, 2008;Dockweiler et al, 2013), electroejaculation (Whitlock et al, 2012), and dehorning however these studies were limited in cattle, and no studies had observed SP response in sheep as an indicator of pain caused by routine husbandry procedures. Hence the lack of homogenous responses in SP and IL-6, and detectable responses in IL-1, β-EP and PGE 2 may not necessarily indicate that these biomarkers are unreliable to detect pain in ruminants if used in other pain models.…”
Section: Castration As a Pain Modelmentioning
confidence: 99%